Development of Problem-Based Learning (PBL) Based Instructional Materials for Automotive Manual Clutch Systems - Vio Lilik Saputra Saputra; Muhamad Amiruddin; Hamid Nasrullah; Bahtiar Wilantara (Jurnal E-Komtek, 2026)
This study aims to develop a Problem Based Learning (PBL) based learning media for the manual clutch system in the Automotive Technology Vocational Education Study Program, Universitas PGRI Yogyakarta. The research used the Research and Development (R&D) method with the 4D model. The teaching aid was developed through design, assembly, and finishing stages using hollow iron. Validation results showed 84% feasibility by media experts, 94% by material experts, and 86.2% by users (very feasible). This media is expected to enhance students’ active understanding through PBL approach before direct practice.